Effect of Thickness on Thin Layer Resistance Value of Zinc Sulfophthalosianin (ZnPcSn) As Prototype of Ozone Detector - Novitasari, Anggriana; Masruroh, Masruroh; Tjahjanto, Rachmat Triandi (Natural B, Journal of Health and Environmental Sciences, 2015)
Thin film of ZnPcSn was developed as a prototype for ozone detector. This study aimed to investigate the relationship thickness of thin film of ZnPcSn along with resistance value toward ozone exposure. The ZnPcSn thin film was deposited on a printed circuit board (PCB) substrate with various thickness using vacuum evaporation technique. The morphology of the thin film was observed using scanning electron microscope (SEM). The SEM images of ZnPcSn thin film showed that thicker layer of thin film leaded to greater pore and uniform distributed layer. To obtain the resistance value, ZnPcSn thin film was exposed to ozone for 30 minutes continuously. Ozone was synthesized by ozonator from air. Thicker film with higher ZnPcSn content had more intensive interaction with ozone. Higher interaction with ozone leaded to the increasing value of generated current, indicated by the decreasing of the thin film resistance value. This result demonstrated Â that the ZnPcSn thin film has promising potential as ozone detector.Â